The Relationship between Spousal Age Difference and Violence against Wife in Nigeria: A Generalized Linear Modelling Approach - Anthony C. Akpanta; Idika E. Okorie; Faith Kanu (Program Studi Statistika Unisba, 2017)
The act of violence against wife is condemnable and attracts various legal penalties, globally. This article attempts to find a link between spousal age difference and violence (Emotional, Physical and Sexual) against wives in Nigeria. The result show that wives who are older than their partners are more likely to experience sexual and emotional violence; also, wives who are same age as their husbands are more likely to experience sexual violence; whereas wives who are 1-4 years younger than their husbands are more likely to experience physical violence; while wives 5 years or more younger than their husbands are generally less likely to experience any form of violence.